2016
DOI: 10.18203/issn.2454-5929.ijohns20162179
|View full text |Cite
|
Sign up to set email alerts
|

Role of high resolution computed tomography in the evaluation of temporal bone lesions: our experience

Abstract: <p class="abstract"><strong>Background:</strong> High resolution computed tomography (HRCT) is a modification of routine computed tomography. It provides visual information of the minute structural details of the temporal bone. The present study aimed at studying the pathological processes of the temporal bone and their extent using HRCT.</p><p class="abstract"><strong>Methods:</strong> This prospective study was done by taking HRCT of the temporal bone in 50 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Similar findings was reported byBagul, (2016) 9 who observed that temporal bone pathologies were more common in male where the gender ratio male:female was 2:1 which closely resembles with the present study.Similarl male predominance was also observed by Jyothi&Shrikrishna (2016), Shankhwar et al (2016) and Viastarakos et al (2012). 12,10,13 In HRCT findings it was observed in this present series that majority (96.9%) patients had soft tissue lesion, followed by 29.2.8% opacified mastoid, 27.7% ossicular and scutum erosion, 4.6% Erosion of tympanic wall, 10.8% erosion of tegmen tympani, 4.6% erosion of vestibule and facial canal and 3.1% erosion of sigmoid sinus plate and 3.1% erosion of lateral semicircular canal. Findings were comparable to the study conducted byBagul (2016)9 which showed thecommon HRCT findings in the cholesteatoma was soft tissue lesion in 100% followed by ossicular and scutum erosion 95%, erosion of tympanic wall 90%, opacified mastoid 57%, erosion of sigmoid plate 42%, erosion of lateral semicircular canal wall and tegmentympanii 19% and erosion of vestibule and fascial canal 9.5%.Cholesteatoma may be associated with extratemporal and intracranial complications, and almost all the complications are usually secondary to bone destruction and infected cholesteatoma, observed by study of Mafee et al 1988).…”
supporting
confidence: 52%
“…Similar findings was reported byBagul, (2016) 9 who observed that temporal bone pathologies were more common in male where the gender ratio male:female was 2:1 which closely resembles with the present study.Similarl male predominance was also observed by Jyothi&Shrikrishna (2016), Shankhwar et al (2016) and Viastarakos et al (2012). 12,10,13 In HRCT findings it was observed in this present series that majority (96.9%) patients had soft tissue lesion, followed by 29.2.8% opacified mastoid, 27.7% ossicular and scutum erosion, 4.6% Erosion of tympanic wall, 10.8% erosion of tegmen tympani, 4.6% erosion of vestibule and facial canal and 3.1% erosion of sigmoid sinus plate and 3.1% erosion of lateral semicircular canal. Findings were comparable to the study conducted byBagul (2016)9 which showed thecommon HRCT findings in the cholesteatoma was soft tissue lesion in 100% followed by ossicular and scutum erosion 95%, erosion of tympanic wall 90%, opacified mastoid 57%, erosion of sigmoid plate 42%, erosion of lateral semicircular canal wall and tegmentympanii 19% and erosion of vestibule and fascial canal 9.5%.Cholesteatoma may be associated with extratemporal and intracranial complications, and almost all the complications are usually secondary to bone destruction and infected cholesteatoma, observed by study of Mafee et al 1988).…”
supporting
confidence: 52%